Crenças de eficácia de gestores escolares e as metas do IDESP - Daniela Couto Guerreiro Casanova; Miguel Henrique Russo (EccoS – Revista Científica)
This research is dedicated to investigate the relationship between principals’ efficacy beliefs and goal achievement for IDESP, the state of São Paulo’s external evaluation of public schools. This research was conducted by means of online resources for data collection, with 228 principals as participants. Data was analyzed by means of quantitative strategies which revealed that age and self-efficacy beliefs for instructional aspects were the variables that most important in explaining the IDESP goal achievement. Through qualitative analysis, it was found that school principals who said they had stronger self-efficacy were those who achieved goals, and obtaining goals was executed due through the involvement of principals with aspects of teaching and learning.